Measuring the Performance of Private Higher Education: Study of Levers of Control in Culture-Based Higher Education (E-Jurnal Akuntansi, 2024)
This research explores in depth the non-financial performance measurement mechanism at one of the private universities (PTS) in Bali Province, including the supporting and inhibiting factors in implementing this mechanism. This research is qualitative research with a case study approach. Institutional theory is used as the main theory of research and is correlated with the levers of control framework. Data was collected by interviews and document analysis and analyzed using narrative, content and discourse analysis methods. The results show that PTS is categorized as a highly regulated institution that creates legitimacy, which is the focus of institutional theory. In the levers of control framework, supporting and inhibiting factors for this mechanism are identified through belief systems, boundary systems, diagnostic control systems, and interactive control systems. This research provides an overview of the mechanism for measuring non-financial performance in private universities which has not been carried out in much previous research.
Keywords: Performance Measurement; Institutional; Legitimation; Levers Of Control